Redes globales de producción, industrialización y desarrollo: el caso de la Industria del Vestido en Yucatán, México - Carlos Enrique Leyva; Felipe Alonzo Solís; Raúl Antonio Vela Manzanilla (Atlantic Review of Economics (ARoEc), 2019)
– It is analyzed, in the current context of economic globalization and through the case of the clothing industry in Yucatan, the territorial dynamics that occur with the insertion of this industry in the Global Production Networks (GPN) and the determinants of the process of economic and social upgrading in the industrialization of Yucatecan territory. For the approximation to the studied reality the methods were used: historical, qualitative, quantitative, comparative and the rational critic; a literature review was made to the data bank of the National Institute of Statistics and Geography and to the available scientific bibliography, as well as a survey by stratified probabilistic sampling in the localities of Mérida, Kimbilá and Tekit. The study concludes that, in the case of Yucatan, the insertion of its clothing industry in the GPN produced greater economic polarization and no greater social cohesion in the state, that its historical-economic, cultural, social and institutional characteristics influenced the way in which it was inserted in these networks and that the main determinants for the industrialization of this territory continue to be endogenous since the economic development of this industry continues to be associated to factors of this type and not to its only insertion in the GPN.
Keywords: F60; F63; F68; O10; 330; Global production networks; industrial upgrading; territorial economic development; clothing industry